A brief cognitive-behavioural treatment approach for PTSD and Dissociative Identity Disorder, a case report. (September 2021) - van Minnen, Agnes; Tibben, Marleen
Abstract: Background and objectives: We described a new treatment model for Posttraumatic Stress Disorder (PTSD) and Dissociative Identity Disorder (DID), based on cognitive-behavioural principles. In this model, dissociation is seen as a maladaptive avoidant coping strategy. In addition, we stress that patients have dysfunctional beliefs about dissociation. Both elements, avoidance behaviour and dysfunctional beliefs, are challenged during the brief, intensive trauma-focused treatment. When the PTSD-symptoms decrease, the patient is offered a fare-well ritual to say goodbye to their identities in one or more additional sessions. Methods: We illustrate this treatment approach with a case report of a woman with PTSD as a result of sexual abuse in her childhood, and DID with four identities. Treatment outcome was measured at intake, at pre-treatment, at post-treatment and at 3 and 6 months follow-up. Results: After the short treatment of only 2 weeks, she no longer fulfilled the DSM-5 diagnostic criteria for PTSD nor DID. These results were maintained at the follow-ups. Limitations: Although we included a baseline-controlled time phase, it was not a controlled study, and only one patient was treated. Conclusions: This new treatment model for DID-patients is promising but results should be interpreted cautiously since we described only one patient. Highlights: Posttraumatic Stress Disorder and Dissociative identity Disorder are comorbid. A brief cognitive behavioural treatment model is illustrated with a case report. Intensive trauma-focused treatment combined with saying farewell ritual. After treatment and 6 months follow-up no longer PTSD or DID diagnosis. This new treatment model is promising for patients with both PTSD and DID.